Peranan Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan Dalam Menerapkan Sikap Nasionalisme Peserta Didik - Titin Anggraeni; Febrian Alwan Bahrudin; Qotrun Nida (Departement of Mathematics Education, 2024)
The root problem of the research is the lack of understanding of the students of national songs and national heroes, where the students are more likely to know and love modern songs than the Indonesian national songs. The purpose of this research was to find out the students’ nationalism attitude through PPKn learning, to find out the obstacles faced by the teacher in applying the nationalism attitude and to find out the effective strategy in applying the nationalism attitude on Grade VIII Students of State Junior High School (SMPN) 1 Mekar Baru. The research method used was descriptive qualitative research and the data collection techniques were interview, observation, and documentation. The research results showed that State Junior High School (SMPN) 1 Mekar Baru in applying the nationalism attitude was not maximal, the obstacle is the limitation of means and facilities in schools, and the strategy to optimize the attitude of nationalism of students is to provide motivation and interesting learning about nationalist attitudes. It can be concluded that the efforts of teachers in applying the attitude of nationalism to the pupils involve consistent training, giving motivation that the importance of nationalist attitudes, cooperation with parents, and the use of various interesting learning strategies.